2019
DOI: 10.1021/acs.chemmater.9b01075
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Protection of Color Dyes Encapsulated by Graphene Barrier Films

Abstract: The decolorization of paintings, photographs, and artworks is a common phenomenon related to the oxidative degradation of color dyes reacting with oxygen or water molecules, which also causes a critical problem in organic light-emitting diodes (OLEDs). It is expected that the gas-impermeable property of graphene and h-BN can be utilized to protect the color dyes from degradation. However, the transfer method has been limited to a polymer with high glass transition temperature (T g) or a glass substrate due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Further, the encapsulation of NOA63 with 3 M tape, silicon nitride (SiN x ) (200 nm) thin film and NOA63 side passivation presented a moderate water vapor transmission rate (WVTR) (3.6 × 10 −2 g m −2 day −1 , Supplementary Fig. 3) as compared with that of the recently introduced 4-6 layers of graphene-encapsulated OLEDs (1.78 × 10 −2 g m −2 day −1 ) 40,41 . Nevertheless, there is a trade-off between encapsulation quality and stretchability.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, the encapsulation of NOA63 with 3 M tape, silicon nitride (SiN x ) (200 nm) thin film and NOA63 side passivation presented a moderate water vapor transmission rate (WVTR) (3.6 × 10 −2 g m −2 day −1 , Supplementary Fig. 3) as compared with that of the recently introduced 4-6 layers of graphene-encapsulated OLEDs (1.78 × 10 −2 g m −2 day −1 ) 40,41 . Nevertheless, there is a trade-off between encapsulation quality and stretchability.…”
Section: Resultsmentioning
confidence: 97%
“…Such layouts demonstrated a shifted EL between the buckled (non-stretched) and planar (stretched) modes, while stretchability of the GSOLEDs were also limited to 50% or less 28,39 . Although the passivation for flexible and stretchable OLEDs have been demonstrated previously [40][41][42] , various approaches of encapsulation for water-proofing, and mechanical analysis of the strain have not been discussed.…”
mentioning
confidence: 99%
“…Two-dimensional materials such as graphene have attracted widespread attention due to their unique properties compared with bulk materials. Two-dimensional materials, which include insulating, semiconducting, metallic, and superconducting materials, have great utilization potential in electrochemistry and optoelectronics due to their distinctive structures and electrical properties. What is more, the electrical performance of RRAMs can be improved and optimized by doping atomic vacancies or metals . Recently, Gogotsi et al revealed that Al can be etched from Ti 2 AlC 3 using hydrochloric acid and a new 2D material Ti 2 C 3 was formed.…”
Section: Introductionmentioning
confidence: 99%
“…The elemental doping of graphene that replaces carbon atoms with boron or nitrogen atoms is very stable and homogeneous, but it lowers charge carrier mobility due to electron scattering around the heteroatoms 182 and decreases electrical conductivity, which is undesirable. In addition, while the non-destructive doping of graphene can be efficiently carried out by molecular dopants and self-assembled monolayers [183][184][185] , it does not last long without proper encapsulation [186][187][188] .…”
Section: [H1] Reproducibility and Data Depositionmentioning
confidence: 99%